THE RELATIONSHIP BETWEEN INTERNAL MARKETING, EMPLOYEE SATISFACTION, AND CUSTOMER SATISFACTION: A VIETNAMESE BANK CASE - Quang, Nguyen Ngoc; Lam, Nguyen Viet; Ha, Nguyen Thai; Lan, Nguyen Thu (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to analyse the relationship between internal marketing, employee satisfaction and customer satisfaction in the banking service. The purpose is to examine the impact of internal marketing on employee and customer satisfaction based on the survey of 10 Vietnamese commercial banks. The research data was collected through a questionnaire with two parts (one for the staff and the other for the client of this interviewed staff) so a pair sample of staffs-clients was constructed. Based on the data collection, the trinity relationship between internal marketing, employee satisfaction and customer satisfaction of Vietnamese banking community is explored. Findings reveal that: (1) internal marketing has a significant and positive impact on both employee satisfaction and customer satisfaction, (2) the employee satisfaction has a significant and positive impact on customer satisfaction and mediates the relationship between internal marketing and customer satisfaction. The results indicate the implication that Vietnamese banking managers should apply internal marketing practices to upgrade employee satisfaction, thus customer satisfaction will be improved in the fiercely competitive service industry.